Microflora, Provision of Ordinary Chernozem with Nutrients and Barley Productivity when Inoculating the “Agrobionov” Preparation - Abilzhan Khussainov; Anar Ayapbergenova; Anara Sarsenova; Yedil Aishuk; Razya Khussainova (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Modern agriculture in Kazakhstan is carried out by an extensive method and accompanied by a noticeable decrease in soil fertility, in particular the biological and agrochemical properties as the main reason of insufficient fertilizer applications. The objectives of the research were to study the Agrobionov doses effect applied during soil preparation on microflora species composition, microbiological activity, availability of plant nutrients in soil, and barley grain yield. The preparation substances are produced from industrial wastes - coal ash, slag and carbon black. The experiments were carried out in the Northern Kazakhstan on the experimental field of Ualikhanov Kokshetau State University. The soil is represented by ordinary chernozem, carbonate, medium-power, lowhumus, heavy-loam. The cellulose-decomposing activity of soil bacteria was determined by the application of flax cloth. Microflora was studied on solid nutrient media, the productivity of barley grain by the continuous method. It has been established that preparation substances promote an increase in the total number of microorganisms, including nitrogen consuming microorganisms, oligonitrophils, phosphorus mobilizing, cellulose-decomposing, fungi, nitrogen nutrition improvement of soil, the increase of grain yield. The preparation substances improve biological properties, nutritional regime of soil, raises barley productivity, and also has ecological significance in terms of production waste utilization.